Embryo incubation by time-lapse systems versus conventional incubators in Chinese women with diminished ovarian reserve undergoing IVF/ICSI: a study protocol for a randomised controlled trial. Issue 11 (14th November 2020) - Chen, Miaoxin; Wu, Yuanyuan; Huang, Xin; Li, Wentao; Sun, Chunyan; Meng, Zhenzhen; Ai, Ai; Hong, Ling; Tang, Chuanling; Li, Kunming; Fu, Yonglun; Chen, Zhiqin; et al.
Abstract : Introduction: The time-lapse imaging system (TLS) is a newly developed non-invasive embryo assessment system. Compared with conventional incubators, a TLS provides stable culture conditions and consistent observations of embryo development, thereby potentially improving embryo quality and selection of the best quality embryo. Although TLSs have been routinely used in many in vitro fertilisation (IVF) centres globally, there is insufficient evidence to indicate that TLSs result in higher cumulative live birth rates over conventional incubators. The purpose of this study is to compare the cumulative live birth rates and safety including miscarriage in infertile patients with diminished ovarian reserve (DOR) from both TLSs and conventional incubators. Methods and analysis: This study is a double-blind randomised controlled clinical trial (1:1 treatment ratio of TLSs vs conventional incubator). A total of 730 patients with DOR undergoing the first or second cycle of IVF or intracytoplasmic sperm injection (ICSI) will be enrolled and randomised into two parallel groups. Participants will undergo embryo culture in the TLSs (group A) or the conventional incubators (group B), respectively. Embryos are selected for transfer in both groups by the morphological characteristics. The embryo selection algorithm software is not used in the TLSs. The primary outcome is the cumulative live birth rate of the trial IVF/ICSI cycle within 12 months after randomisation. This study is powered to detect an absolute difference of 10% (35% vs 25%) at the significance level of 0.05% and 80% statistical power based on a two-sided test. Ethics and dissemination: This trial has been approved by the Institutional Ethical Committee of Shanghai First Maternity and Infant Hospital (KS1958). All participants in the trial will provide written informed consent. The study will be conducted according to the principles outlined in the Declaration of Helsinki and its amendments. Results of this study will be disseminated in peer-reviewed scientific journals. Trial registration number: Chinese Clinical Trial Registry (ChiCTR1900027746).